2021
DOI: 10.1002/2688-8319.12041
|View full text |Cite
|
Sign up to set email alerts
|

Ten principles for generating accessible and useable COVID‐19 environmental science and a fit‐for‐purpose evidence base

Abstract: 1. The 'anthropause' , a period of unusually reduced human activity and mobility due to COVID-19 restrictions, has serendipitously opened up unique opportunities for research on how human activities impact the environment. 2. In the field of health, COVID-19 research has led to concerns about the quality of research papers and the underlying research and publication processes due to accelerated peer review and publication schedules, increases in pre-prints and retractions. 3. In the field of environmental scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…The use of knowledge brokers (i.e., bridging agents, evidence bridges-see Kadykalo et al 2021b) embedded within agencies are (and were) recommended (see Cook et al 2013;Cvitanovic et al 2015;Roux et al 2019) as a means of mitigating several of the barriers identified in our study: limited access to journals/articles and information overload, as well as resource and time limitations. Other mitigations strategies to removing barriers to accessing WBS in NRM include furtherdeveloped hyperlinked 'controlled vocabularies', onepage scientific summaries translated for multidisciplinary audiences, and key visuals (Sutherland and Wordley 2018;Kadykalo et al 2021c). For example, I'm noticing the younger generation really relying on visuals, and not so much the journals.…”
Section: Discussionmentioning
confidence: 99%
“…The use of knowledge brokers (i.e., bridging agents, evidence bridges-see Kadykalo et al 2021b) embedded within agencies are (and were) recommended (see Cook et al 2013;Cvitanovic et al 2015;Roux et al 2019) as a means of mitigating several of the barriers identified in our study: limited access to journals/articles and information overload, as well as resource and time limitations. Other mitigations strategies to removing barriers to accessing WBS in NRM include furtherdeveloped hyperlinked 'controlled vocabularies', onepage scientific summaries translated for multidisciplinary audiences, and key visuals (Sutherland and Wordley 2018;Kadykalo et al 2021c). For example, I'm noticing the younger generation really relying on visuals, and not so much the journals.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasis is not unexpected given that early COVID-19 research has been largely opportunistic [34]. Indeed, many publications on the (ecological) impacts of COVID-19 were produced very rapidly early on in the pandemic [35], but when synthesized later, suggest truly mixed effects [32]. Moreover, as we emphasized, policy responses to the pandemic have focused singularly on human resilience and have been relatively reactive and unplanned.…”
Section: Social-ecological Impacts Of the Covid-19 Pandemicmentioning
confidence: 76%
“…Currently, there is no established CEE framework for this process; however, it is common in the healthcare field and guidance has been developed in that realm (Moher and Tsertsvadze, 2006;Garner et al, 2016; also see 3 Final remarks for suggestions for future work below). This has become particularly salient during the COVID-19 pandemic where vast amounts of new knowledge are being generated rapidly (Tricco et al, 2020), with lessons emerging that are relevant to environmental evidence synthesis (Kadykalo et al, 2021).…”
Section: What To Do When the Evidence Base Is Ambiguous?mentioning
confidence: 99%